Impacts of Sub-lethal DDT Exposures on microRNA and Putative Target Transcript Expression in DDT Resistant and Susceptible Drosophila melanogaster Strains - Seong, Keon Mook; Coates, Brad S.; Pittendrigh, Barry R. (Frontiers in Genetics, 2019)
Ten constitutively differentially expressed miRNAs were previously described between DDT-resistant 91-R and -susceptible control Drosophila melanogaster strains, and among their predicted target genes were those associated with metabolic DDT resistance mechanisms. The present study evaluated the inducibility of miRNA expression and putative downstream regulation of cytochrome P450s in response to DDT exposure in a time-dependent manner in 91-R and the susceptible Canton-S strain. Specifically, RT-qPCR analysis showed that DDT exposures led to the significant down-regulation (repression) of miR-310-3p, miR-311-3p, miR-312-3p, miR-313-3p, and miR-92a-3p levels in Canton-S. This is contrasted with the lack of significant changes in 91-R at most time-points following DDT exposure. The levels of expression among miRNAs exhibited opposite expression patterns compared to their corresponding putative target cytochrome P450s at the same time points after DDT exposure. Collectively, results from this study suggest that miR-310-3p, miR-311-3p, miR-312-3p, miR-313-3p, and miR-92a-3p might have a potential role in the control of DDT detoxification through the post-transcriptional regulation of target cytochrome P450s in Canton-S. Conversely, the lack of significant changes of these same miRNAs in 91-R following DDT-exposure suggests a possible adaptive mutation that removes repressive control mechanisms. These data are important for the understanding impact of adaptive changes in miRNA expression on post-transcriptional regulatory mechanism involved in the evolution of DDT resistance in 91-R.